Study on the seismic performance of retrofitted RC frames with RC infill wall mega braces. (15th April 2021) - Cheng, Shao-Ge; Zhu, Yi-Xiu; Zhang, Wei-Ping; Shi, Tie-Hua
Highlights: Novel arrangement of RC infill walls proved capable of upgrading seismic performance of buildings. RC frames retrofitted with infill wall mega braces excel in shaking table tests. Braced RC infill walls absorb bulk of seismic damage reducing damage to outer frame. Abstract: This paper proposes a novel arrangement of RC infill walls made possible by RC infill wall mega braces (RCIWMBs). The seismic behavior of a reinforced concrete (RC) frame structure retrofitted by the RCIWMB was investigated through 1/5-scale shaking table tests. The seismic damage characteristics and the dynamic responses of the model structure under different input ground motions are presented in detail. The results show that the presence of the RCIWMB has a slight effect on the failure of beam-column joints, but it can lead to punching shear failure of its connected frame columns. When the RC walls are arranged diagonally, the RCIWMB can form a macroscopic brace effect, serving as the first seismic line of defense. Compared with traditional RC infill wall retrofitted frame structures, the drawback is obvious failure, which appears on the lower stories of this novel type of structure and is prone to forming a weak story. This indicates a poor structural story ductility and more severe damage to the integral structure. However, the addition of the RCIWMB resulted in a substantial increase in the integral lateral bearing capacity, integral lateral stiffness and integral ductile behavior, a decrease in lateral displacement, and a reduction in damage to the original frame structure. The novel structural system performed better under extensive seismic tests, providing a new method for upgrading the seismic performance of existing buildings.